The Influence Of Gamification, Exclusive Promotions, And Consumer Trust On Customer Loyalty In Shopee E-Commerce (A Case Study Of Unived Bengkulu Students) - Vandri Salomo Lumban Gaol; Tito Irwanto; M. Rahman Febliansa (Jurnal Pakar Manajemen, 2026)
This study aims to determine the influence of gamification, exclusive promotions, and consumer trust on Shopee customer loyalty among students of Universitas Dehasen Bengkulu. The background of this research is based on the increasing competition among e‑commerce platforms that demands innovation in retaining user loyalty, where Shopee presents gamification features and exclusive promotions as its main strategies. The research method used a quantitative approach with descriptive and associative study types. The study sample consisted of 100 respondents who were active students of Universitas Dehasen Bengkulu and active Shopee users. Data were collected via an online questionnaire using Google Forms, then analyzed with the help of SPSS version 22 through validity and reliability tests, as well as multiple linear regression analysis to determine the influence of each variable. The results show that, partially, the variables gamification (X₁), exclusive promotions (X₂), and consumer trust (X₃) significantly influence customer loyalty (Y), with significance values of 0.044; 0.032; and 0.017 respectively (< 0.05). Simultaneously, the three variables significantly affect customer loyalty with an R² value of 0.698, meaning 69.8% of the variation in customer loyalty can be explained by these three independent variables. Based on the results, it can be concluded that gamification, exclusive promotions, and consumer trust play important roles in increasing Shopee customer loyalty. These findings imply that enhancing interaction, trust, and an engaging shopping experience can be effective strategies for retaining customers amid increasingly intense digital competition.